Makna Satire Tersembunyi dalam Iklan (Analisis Semiotika Roland Barthes pada Iklan A Mild Versi Bukan Main) - Stephen Jaufarry; Lusia Savitri Setyo Utami (Koneksi, 2022)
This research discusses the hidden meaning of satire in the Bukan Main version of A Mild advertisement. Today many social problems occur in Indonesian society, such as violations of rules and ethics that have been established by the community. Regarding these social problems, A Mild's product made an advertisement with the title Bukan Main to insult the Indonesian people who violated the rules. Based on this background, this research's problem formulation is how the meaning of satire is depicted in the Bukan Main version of A Mild advertisement. The research objective is to find out and describe the satire's meaning in the advert A Mild version of not playing. The theoretical review used is advertising, semiotics, and satire. This study using a qualitative approach with Roland Barthes' semiotic analysis. The meaning of satire is obtained from a multilevel meaning; this idea is known as the "order of signification," which includes denotation (real meaning) and connotation (multiple meanings) and then ends in myth. This study's results indicate myths such as not caring about others, not caring about the environment, not being disciplined, and problems with social status. The conclusion is that the Bukan Main version of A Mild's ad has a hidden satire meaning that people are still not aware of and behave following existing norms or regulations.Penelitian ini membahas tentang makna satire tersembunyi dalam iklan A Mild versi Bukan Main. Pada masa sekarang banyak terdapat masalah sosial yang terjadi di masyarakat Indonesia seperti pelanggaran aturan dan etika yang sudah ditetapkan oleh masyarakat. Melihat permasalahan sosial tersebut maka produk A Mild membuat iklan dengan judul Bukan Main untuk menyindir masyarakat Indonesia yang melanggar aturan. Rumusan masalah penelitian ini adalah bagaimana makna satire yang digambarkan dalam iklan A Mild versi Bukan Main. Tujuan penelitian adalah untuk mengetahui dan mendeskripsikan makna satire yang digambarkan dalam iklan A Mild versi Bukan Main. Tinjauan teoritis yang digunakan adalah periklanan, semiotika dan satire. Penelitian ini menggunakan pendekatan kualitatif dengan analisis semiotika Roland Barthes. Makna satire tersebut diperoleh dari pemaknaan bertingkat, gagasan ini di kenal dengan istilah order of signification yaitu yang mencakup denotasi (makna sesungguhnya) dan konotasi (makna ganda) lalu berujung pada mitos. Hasil penelitian ini menunjukan mitos seperti kurang peduli dengan orang lain, tidak peduli lingkungan, tidak disiplin, dan masalah status sosial. Kesimpulannya, dalam iklan A Mild versi Bukan Main terdapat makna satire tersembunyi bahwa masyarakat masih belum menyadari dan berperilaku sesuai dengan norma-norma atau peraturan yang ada.